Cultural Intelligence and Openness to Experiences Pave the Way for Cognitive Engagement in Intercultural Group Work. (May 2023) - Poort, Irene; Jansen, Ellen; Hofman, Adriaan
To prepare students for an increasingly globalized world, intercultural group work (IGW) holds promise as a pedagogical tool, because it may help them develop intercultural competence and second-language proficiency. These skills also are needed to complete the discipline-specific aspects of group work successfully. This study investigates the extent to which cultural intelligence (CQ), English language proficiency, and personality contribute to students' cognitive engagement in IGW. A questionnaire was completed by 846 students from six universities in the Netherlands and Canada. Structural equation modeling analyses revealed that CQ and the personality trait of openness are the strongest predictors of cognitive engagement. English language proficiency is a relatively weak predictor. The development of CQ thus should be actively promoted to enhance students' cognitive engagement in IGW.